Identification of Nuclearity of Chromium Binary Adducts with DNA by Negative Ion Mass Spectrometry: Short Communication - Kaleb Kovitch; Qiaoli Liang; Katie Repke; Elizabeth K. Atkinson; Stephen A. Woski; John B. Vincent (Biological Trace Element Research, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Little clams with big potential: nutrient release by invasive Corbicula fluminea can exceed co-occurring freshwater mussel (Unionidae) assemblages - Garrett W. Hopper; Jonathan K. Buchanan; Irene Sánchez González; Megan E. Kubala; Jamie R. Bucholz; Matthew B. Lodato; Jeffrey D. Lozier; Carla L. Atkinson (Biological Invasions, 2022)

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Chronically elevated depressive symptoms interact with acute increases in inflammation to predict worse neurocognition among people with HIV - Rowan Saloner; Emily W. Paolillo; Robert K. Heaton; David J. Grelotti; Murray B. Stein; Andrew H. Miller; J. Hampton Atkinson; Scott L. Letendre; Ronald J. Ellis; Igor Grant; Jennifer E. Iudicello; David J. Moore (Journal of NeuroVirology, 2021)

Biomass distribution of fishes and mussels mediates spatial and temporal heterogeneity in nutrient cycling in streams - Garrett W. Hopper; Keith B. Gido; Caryn C. Vaughn; Thomas B. Parr; Traci G. Popejoy; Carla L. Atkinson; Kiza K. Gates (Oecologia, 2018)

Accounting for the Impact of Conservation on Human Well‐Being - E.J. MILNER‐GULLAND; J.A. MCGREGOR; M. AGARWALA; G. ATKINSON; P. BEVAN; T. CLEMENTS; T. DAW; K. HOMEWOOD; N. KUMPEL; J. LEWIS; S. MOURATO; B. PALMER FRY; et al. (Conservation Biology, 2014)
Conservationists are increasingly engaging with the concept of human well‐being to improve the design and evaluation of their interventions. Since the convening of the influential Sarkozy Commission in 2009, development researchers have been refining conceptualizations and frameworks to understand and measure human well‐being and are starting to converge on a common understanding of how best to do this. In conservation, the term human well‐being is in widespread use, but there is a need for guidance on operationalizing it to measure the impacts of conservation interventions on people. We present a framework for understanding human well‐being, which could be particularly useful in conservation. The framework includes 3 conditions; meeting needs, pursuing goals, and experiencing a satisfactory quality of life. We outline some of the complexities involved in evaluating the well‐being effects of conservation interventions, with the understanding that well‐being varies between people and over time and with the priorities of the evaluator. Key challenges for research into the well‐being impacts of conservation interventions include the need to build up a collection of case studies so as to draw out generalizable lessons; harness the potential of modern technology to support well‐being research; and contextualize evaluations of conservation impacts on well‐being spatially and temporally within the wider landscape of social change. Pathways through the smog of confusion around the term well‐being exist, and existing frameworks such as the Well‐being in Developing Countries approach can help conservationists negotiate the challenges of operationalizing the concept. Conservationists have the opportunity to benefit from the recent flurry of research in the development field so as to carry out more nuanced and locally relevant evaluations of the effects of their interventions on human well‐being. Consideración del Impacto de la Conservación sobre el Bienestar Humano

Exploring the spatio-temporal relationship between two key aeroallergens and meteorological variables in the United Kingdom - Nabaz Khwarahm; Jadunandan Dash; Peter M. Atkinson; R. M. Newnham; C. A. Skjøth; B. Adams-Groom; Eric Caulton; K. Head (International Journal of Biometeorology, 2014)

A meta-analytic approach to quantify the dose–response relationship between melatonin and core temperature - K. Marrin; B. Drust; W. Gregson; G. Atkinson (European Journal of Applied Physiology, 2013)

Diurnal variation in the salivary melatonin responses to exercise: relation to exercise-mediated tachycardia - K. Marrin; B. Drust; W. Gregson; C. J. Morris; N. Chester; G. Atkinson (European Journal of Applied Physiology, 2011)

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

Cadmium, Copper, Iron, and Zinc Concentrations in Kidneys of Grey Wolves, Canis lupus, from Alaska, Idaho, Montana (USA) and the Northwest Territories (Canada) - S. R. Hoffmann; S. A. Blunck; K. N. Petersen; E. M. Jones; J. C. Koval; R. Misek; J. A. Frick; H. D. Cluff; C. A. Sime; M. McNay; K. B. Beckman; M. W. Atkinson; et al. (Bulletin of Environmental Contamination and Toxicology, 2010)

Coral disease following massive bleaching in 2005 causes 60% decline in coral cover on reefs in the US Virgin Islands - J. Miller; E. Muller; C. Rogers; R. Waara; A. Atkinson; K. R. T. Whelan; M. Patterson; B. Witcher (Coral Reefs, 2009)

Production of transgenic pineapple (Ananas cosmos (L.) Merr.) plants via adventitious bud regeneration - M.-L. Wang; G. Uruu; L. Xiong; X. He; C. Nagai; K. T. Cheah; J. S. Hu; G.-L. Nan; B. S. Sipes; H. J. Atkinson; P. H. Moore; K. G. Rohrbach; et al. (In Vitro Cellular & Developmental Biology - Plant, 2009)

Thermal acclimation of leaf and root respiration: an investigation comparing inherently fast‐ and slow‐growing plant species - B. R. LOVEYS; L. J. ATKINSON; D. J. SHERLOCK; R. L. ROBERTS; A. H. FITTER; O. K. ATKIN (Global Change Biology, 2003)
We investigated the extent to which leaf and root respiration ( R ) differ in their response to short‐ and long‐term changes in temperature in several contrasting plant species (herbs, grasses, shrubs and trees) that differ in inherent relative growth rate (RGR, increase in mass per unit starting mass and time). Two experiments were conducted using hydroponically grown plants. In the long‐term (LT) acclimation experiment, 16 species were grown at constant 18, 23 and 28 °C. In the short‐term (ST) acclimation experiment, 9 of those species were grown at 25/20 °C (day/night) and then shifted to a 15/10 °C for 7 days. Short‐term Q 10 values (proportional change in R per 10 °C) and the degree of acclimation to longer‐term changes in temperature were compared. The effect of growth temperature on root and leaf soluble sugar and nitrogen concentrations was examined. Light‐saturated photosynthesis (A sat ) was also measured in the LT acclimation experiment. Our results show that Q 10 values and the degree of acclimation are highly variable amongst species and that roots exhibit lower Q 10 values than leaves over the 15–25 °C measurement temperature range. Differences in RGR or concentrations of soluble sugars/nitrogen could not account for the inter‐specific differences in the Q 10 or degree of acclimation. There were no systematic differences in the ability of roots and leaves to acclimate when plants developed under contrasting temperatures (LT acclimation). However, acclimation was greater in both leaves and roots that developed at the growth temperature (LT acclimation) than in pre‐existing leaves and roots shifted from one temperature to another (ST acclimation). The balance between leaf R and A sat was maintained in plants grown at different temperatures, regardless of their inherent relative growth rate. We conclude that there is tight coupling between the respiratory acclimation and the temperature under which leaves and roots developed and that acclimation plays an important role in determining the relationship between respiration and photosynthesis.

Response of freshwater microcosm communities to nutrients, fish, and elevated temperature during winter and summer - D. McKee; D. Atkinson; S. E. Collings; J. W. Eaton; A. B. Gill; I. Harvey; K. Hatton; T. Heyes; D. Wilson; B. Moss (Limnology and Oceanography, 2003)
Under conditions of stress, shallow freshwater ecosystems can undergo a state change characterized by the rapid loss of macrophytes and subsequent dominance of phytoplankton. Elevated water temperature may promote such change. Here we report the impact of two warming regimes (continuous 3°C above ambient and 3°C above ambient during summer only), with two nutrient loadings and the presence or absence of fish, on 48 microcosm ecosystems created to mimic shallow pond environments. We found that warming did not significantly encourage phytoplankton blooms, even in combination with increased nutrients and fish. Instead, macrophyte communities remained dominant. Macrophyte‐associated invertebrates (gastropods and ostracods) increased in numbers in the warmed microcosms, potentially helping to stabilize the macrophyte communities. Nevertheless, warming produced trends in water chemistry that could be problematic. It increased phosphorus concentrations, total alkalinity, and conductivity. It decreased pH and oxygen saturation and increased the frequency of severe deoxygenation. These trends were largely independent of the other experimental treatments and support the suggestion that moderate warming has the potential to exacerbate existing eutrophication problems.

Feeding and energy budgets of Antarctic krill Euphausia superba at the onset of winter—II. Juveniles and adults - A. Atkinson; B. Meyer; D. Stuϋbing; W. Hagen; K. Schmidt; U. V. Bathmann (Limnology and Oceanography, 2002)
The overwintering success of Euphausia superba is a key factor that dictates population size, but there is uncertainty over how they cope with the scarcity of pelagic food. Both nonfeeding strategies (reduced metabolism, lipid use, or shrinkage in size) and switching to other foods (carnivory, ice algae, or detritus) have been suggested. We examined these alternatives in the southwest Lazarev Sea in autumn (April 1999), when sea ice was forming and phytoplankton was at winter concentrations. Both juveniles and adults had a very high lipid content (36% and 44% of dry mass, respectively) of which >40% was phospholipid. However, their low O:N ratios suggested that these reserves were not being used. Results from gut contents analysis and large volume incubations agreed that juveniles fed mainly on phytoplankton and adults fed on small (

Machine vision for dimensional measurements in mines - R. Singh; D. P. Chapman; K. B. Atkinson (Geotechnical and Geological Engineering, 1997)

Machine vision for dimensional measurements in mines - R. Singh; D. P. Chapman; K. B. Atkinson (Geotechnical and Geological Engineering, 1997)

Digital photogrammetry based automatic measurement of sandstone roof of a mine - Rajendra Singh; D P Chapman; K B Atkinson (Journal of the Indian Society of Remote Sensing, 1997)